2020
DOI: 10.1007/s00421-020-04567-3
|View full text |Cite
|
Sign up to set email alerts
|

The knowns and unknowns of neural adaptations to resistance training

Abstract: The initial increases in force production with resistance training are thought to be primarily underpinned by neural adaptations. This notion is firmly supported by evidence displaying motor unit adaptations following resistance training; however, the precise locus of neural adaptation remains elusive. The purpose of this review is to clarify and critically discuss the literature concerning the site(s) of putative neural adaptations to short-term resistance training. The proliferation of studies employing non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 106 publications
2
66
0
2
Order By: Relevance
“…Previous studies reported that resistance exercise, even at low intensity, improves exercise tolerance [ 19 ]. The improvement in physical function with resistance training in the early phase is considered to be a result of neural adaptations and may be associated with an increase in motor units [ 20 , 21 ]. Resistance exercise was shown to be significantly and positively related to 6MWT at hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that resistance exercise, even at low intensity, improves exercise tolerance [ 19 ]. The improvement in physical function with resistance training in the early phase is considered to be a result of neural adaptations and may be associated with an increase in motor units [ 20 , 21 ]. Resistance exercise was shown to be significantly and positively related to 6MWT at hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training is known to increase maximal force generating capacity of muscle when performed regularly (27). The initial (<2-4 weeks) increases in muscle force production following resistance training are thought to be primarily underpinned by neural factors (60), followed by adaptation in muscle morphology (>5-8 weeks;…”
Section: Introductionmentioning
confidence: 99%
“…Although the specific neural loci remain opaque, the motor cortex is thought to play a fundamental role in the control of movements, from the generation of 'low-level' control signals such as muscle force production (Evarts, 1968;Cheney & Fetz, 1980; and see Omrani et al, 2017 for a review) to involvement in 'high-level' control functions such as motor skill acquisition and consolidation (Papale & Hooks, 2018). The motor cortex therefore seems a plausible site of nervous system adaptation with changes in the excitatory and/or inhibitory intracortical circuits that appear to mediate increases in force generation after RT (for reviews, see Kidgell et al, 2017;Skarabot et al, 2020) and decreases in strength after disuse (Clark et al, 2010). An enhanced understanding of the modulations in the motor cortex following RT may help to improve and refine the exercise prescription of RT, which is now part of the physical activity recommendations for the general populations as well as people with neurological disorders (Kim et al, 2019;Verschuren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%